Contributions of the SocialNEET project to the development of skills for active life - Costa, Juliana (2022)
The SocialNEET project, promoted at the Polytechnic Institute of Bragança, between November 2020 and February 2021, whose main goal is the (re)integration in the labour market of young people, through the creation of innovative social business solutions and finding employment in companies or associations in the social sector. It provides learning for active life and education for entrepreneurship, through the participation of facilitators (students of higher education) who will simplify the connection between mentors (successful entrepreneurs and consultants) and young NEET (not in education, employment or training), in the sense of creating life projects, social projects or innovative social business and job search solutions in companies or associations in the social sector. The essential focus of this article corresponds on the training of facilitators (N=10) and its objective is to understand the capacities developed by them in this process, as well as the limitations felt and the strategies to minimize them. For this purpose, a qualitative case study was carried out based on the documentary analysis of the training, namely an observation grid, a questionnaire to the trainees and the reflective analysis of the trainers. We conclude that the strengthening of soft skills, intercultural communication and education for entrepreneurship may be the priority ways to promote social improvements and thus contribute to the 2030 Agenda.